On Î±- Ï„-disconnectedness and Î±- Ï„-connectedness in topological spaces - Mishra, Sanjay (Acta Scientiarum. Technology, 2015)
The aims of this paper is to introduce new approach of separate sets, disconnected sets and connected sets called Î±- Ï„-separate sets, Î±- Ï„-disconnected sets and Î±- Ï„-connected sets of topological spaces with the help of Î±-open and Î±-closed sets. On the basis of new introduce approach, some relationship of Î±- Ï„-disconnected and Î±- Ï„-connected set with Î±- Ï„-separate sets have been investigated thoroughly. Â